2021
DOI: 10.17770/sie2021vol5.6252
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges of Organizing and Implementing Distance Pre-School Education: Teachers’ Opinions

Abstract: The Council of the European Union (2020) points out that the COVID-19 pandemic has had a major impact on education and teaching systems and has fundamentally changed the way we learn, teach, communicate and collaborate within and between our education and teaching communities. The aim of this study is to explore the opinion of pre-school teachers on the opportunities and challenges faced by them in organizing and conducting pre-school education at a distance. The strategy of qualitative research was chosen for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…On the other hand, the respondents in this study believed that parents and families have an important role in some tasks and activities with their children. Similar findings by Braslauskienė et al (2021) showed that preschool teachers were constantly engaged in mutual communication with learners' parents to provide them with instructional materials. Undoubtedly, the Covid-19 pandemic has created anxiety for children, families, and educators alike.…”
Section: Discussionsupporting
confidence: 55%
“…On the other hand, the respondents in this study believed that parents and families have an important role in some tasks and activities with their children. Similar findings by Braslauskienė et al (2021) showed that preschool teachers were constantly engaged in mutual communication with learners' parents to provide them with instructional materials. Undoubtedly, the Covid-19 pandemic has created anxiety for children, families, and educators alike.…”
Section: Discussionsupporting
confidence: 55%
“…In the qualitative research project of Atiles, Almodóvar, Vargas, Dias & León, which was implemented in 7 countries of South America deploying the tool of semi-structured interviews, kindergarten teachers implemented the ERT by distributing printed worksheets and other printed educational material, sending digital material and educational instructions via e-mail, telephone, or other commercial platforms such as WhatsApp (Atiles, Almodóvar, Vargas, Dias & León, 2021). Similar techniques and the use of the same or similar social platforms such as Viber or unofficial educational platforms like Google Classroom were mentioned also in other studies that focused on the implementation of ERT in kindergarten in various countries such as China (Hu, Chiu, Leung & Yelland, 2021), Lithuania (Braslauskienė, Jacynė, Norviliene, Ramanauskienė, & Strazdienė, 2021) and an island state in the Pacific (Dayal & Tiko, 2020). Some preschool teachers differentiated from asynchronous education and they deployed teleconferencing platforms such as Skype or Zoom, to do synchronous classes and promote the interaction and communication of the children.…”
Section: The Implementation Of Ert In Preschool Educationmentioning
confidence: 96%